Analysis the Ability of Islamic Education Teacher in Comprehending the Procedure to Make Learning Evaluation - Zulfani Sesmiarni; Iswantir Iswantir; Ilian Ikhsan; Yasmansyah Yasmansyah (AL-ISHLAH: Jurnal Pendidikan, 2022)
Teachers’ competence in creating an achievement test is a kind of important competence in managing teaching and learning processes. This article aims to explain the analysis of Islamic religious teachers in creating an achievement test. The data were gathered through questionnaires which were distributed to 320 Islamic religious teachers who teach at various level of education. The result shows that teachers’ competence in planning evaluation procedure was below 78%. Meanwhile, the highest indicator was on determining the materials for the test which done at the beginning of the test, which was 77.5%. On the other hand, the lowest percentage was on doing try out which was 26,3%. It shows that the tests which were created by the teachers still need certain improvements so that it can meet the requirements. The results of this research describe that the competence of Islamic religious teachers in comprehending the evaluation procedure was still low. It is necessary to provide knowledge and comprehension in order to implementing a properly and in accordance with appropriate procedures of an evaluation. Islamic religious teachers should deeply develop their competence in evaluation. This research is only limited to the ability in planning evaluation by Islamic religious education teachers. Furthermore, further research is needed that examines the ability of teachers in the evaluation and follow-up stages of evaluation.